2022
DOI: 10.3390/nu14173567
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil (EVOO), a Mediterranean Diet Component, in the Management of Muscle Mass and Function Preservation

Abstract: Aging results in a progressive decline in skeletal muscle mass, strength and function, a condition known as sarcopenia. This pathological condition is due to multifactorial processes including physical inactivity, inflammation, oxidative stress, hormonal changes, and nutritional intake. Physical therapy remains the standard approach to treat sarcopenia, although some interventions based on dietary supplementation are in clinical development. In this context, thanks to its known anti-inflammatory and antioxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 135 publications
0
13
0
Order By: Relevance
“…Lipid depots between and within muscle cells (myosteatosis) cause a “perfect storm” of mitochondrial dysfunction, increased oxidative stress, diminished insulin resistance, increased systemic inflammation, lipotoxicity, fiber atrophy, and damage to satellite cells [ 79 ]. Data also suggest that certain Mediterranean diet components, such as extra virgin olive oil, may increase the production of insulin-like growth factor 1 (IGF1) [ 80 ]. IGF1 is a hormone that regulates prenatal development, child growth, and muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid depots between and within muscle cells (myosteatosis) cause a “perfect storm” of mitochondrial dysfunction, increased oxidative stress, diminished insulin resistance, increased systemic inflammation, lipotoxicity, fiber atrophy, and damage to satellite cells [ 79 ]. Data also suggest that certain Mediterranean diet components, such as extra virgin olive oil, may increase the production of insulin-like growth factor 1 (IGF1) [ 80 ]. IGF1 is a hormone that regulates prenatal development, child growth, and muscle regeneration.…”
Section: Discussionmentioning
confidence: 99%
“… 45 , 46 EVOO, as the main source of MUFA in the diet, can play a significant role in weight gain, reducing muscle mass and fat mass wasting, and improving nutritional status in cancer patients. 47 Studies have shown that hydroxytyrosol, as one of the main components of EVOO, prevents muscle wasting by inhibiting reactive oxygen species (ROS) and increasing antioxidant capacity. 47 The levels of oxidizing compounds such as ROS increase in cancer cachexia, and with the progress of cachexia, cell damage and inflammation cause disease deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Camajani et al [ 43 ] described the beneficial effects of the VLCKD combined with physical exercise in reducing FM, improving metabolic profile, and preserving skeletal muscle performance in a woman with sarcopenic obesity two weeks after hospitalization for severe COVID-19 disease. In the context of a link between the inflammatory status and FFM, a very recently published study reported the benefits of dietary n-3 polyunsaturated fatty acids for muscle function in healthy older adults to target inflammation and to improve the “anabolic resistance” to exercise associated with aging [ 44 ], while an extensive review examined the anti-inflammatory and antioxidative properties of extra virgin olive oil in delaying/preventing loss of muscle mass and function [ 45 ].…”
Section: Discussionmentioning
confidence: 99%